Climate governance at the fringes: Peri-urban flooding drivers and responses. (June 2022) - Winter, Amanda K.; Karvonen, Andrew
Abstract: There is a large body of scientific evidence on the climate crisis and flooding in urban areas. Extreme weather events are producing extensive property damage and loss of life and require new modes of flood governance. However, the climate crisis does not stop at the city limits: peri-urban areas have related but distinct flood challenges due to land use change, regulation, perceptions, and capacity to develop collective responses. The aim of the literature review is to synthesize peri-urban flood governance drivers and responses with a particular emphasis on empirical findings from the past decade. The literature review draws on findings from 26 empirical case studies with respect to how and where research is conducted on peri-urban flood governance, the drivers of peri-urban flooding, and the responses by peri-urban stakeholders to address flood risks. A common governance approach involves autonomous adaptation that results in maladaptation – both of which are critiqued as inadequate to address flood risks. The findings reveal a host of specific peri-urban challenges in addressing flooding but also point towards opportunities for new modes of adaptive governance. The article concludes by reflecting on the promise of developing an adaptive governance approach to peri-urban flooding to acknowledge the social and ecological complexities of climate change while opening up possibilities for emergent modes and innovative approaches of collaborative problem-solving. Highlights: Literature review synthesizes findings from 26 cases of peri-urban flood governance. Many cases in informal settlements using autonomous adaptation protection measures. Distinct challenges due to land use change, regulation, perceptions, and capacity. Reflect on the promise of an adaptive governance approach to peri-urban flooding.